PENGARUH FASILITAS KERJA, KEDISIPLINAN DAN PENGAWASAN TERHADAP KINERJA PEGAWAI DINAS PERIKANAN KOTA TANJUNGBALAI - Elfina Manurung; Eko Topan Prihatin Nura; Nurdin .; Tengku Anggi Metia; Isminingsih . (Manajemen dan Bisnis, 2021)
The  formulation  of  the  problem  in  this  research  is:  How  do  work  facilities, discipline   and   supervision   influence   the   employees   performance   at   Dinas Perikanan  Kota Tanjungbalai.  This study aims to determine  the effect of work facilities,   discipline   and  supervision   on  employee   performance.   With   total sampling technique, the sample in this study was 41 people. The results showed; Work  facilities   partially   have  a  positive   effect  on  employee   performance; Discipline partially has a positive effect on employee performance; Partial supervision has a positive effect on employee performance; Work facilities, discipline and supervision have a positive and significant effect on employee performance.